NATURAL TOURIST RESOURCES OF KHATIRCHI DISTRICT OF NAVOI REGION - Ziyadullayeva Sevara Begali Kizi; Amriddinova Rayhona Sadriddinovna (Journal of Higher Education and Academic Advancement, 2024)
Navoi region is one of the regions with great tourist potential, but it is not fully utilized. The area has ecological, geological, historical, archaeological, architectural, recreational, health, gastronomic, and monumental tourist resources. In particular, we will analyze the possibilities of attracting tourists to the natural resources of the Khatirchi district of the region.